Right Ventricular Myocardial Ischemia with Arrhythmia in an Asphyxiated Newborn - Anne Lee Solevåg; Georg M. Schmölzer; Po-Yin Cheung (Thieme Medical Publishers, Inc., 2016)
Abstract Background Infant and neonatal myocardial infarction (MI) has been described in association with congenital heart disease, coronary artery abnormalities, myocarditis, and tumors. MI in the perinatal period in a structurally normal heart and with ventricular arrhythmia as a presenting feature has not been thoroughly described. Published case reports describe treatment methods extrapolated from adult MI. However, due to the rare occurrence, the most appropriate acute treatment for both MI and ventricular arrhythmia in newborn infants remains unknown. Case A male term infant with perinatal asphyxia and need for extensive cardiopulmonary resuscitation at birth had ventricular tachyarrhythmia and ST-elevations on electrocardiogram. Four hours after birth, he died from cardiogenic failure. A thrombus at the right coronary artery was found on autopsy. Conclusion MI in the perinatal period in a structurally normal heart is very rare and mortality is high. Although acute treatments extrapolated from adult MI has been described to result in favorable outcomes in newborn infants, guidelines are lacking on how to manage acute MI and associated ventricular arrhythmia.